Modelling dynamic systems - Basic aspect and application to performance analysis - Perl, J. (International Journal of Computer Science in Sport, 2004)
Because of their complex internal interactions, the time-dependent behaviour of dynamic systems cannot be predicted using static description models only, if a sufficient quality of prediction is expected. Instead, models have to be developed that reflect the system dynamics and help to simulate its behaviour. Whether such a model is sufficient and adequate has to be decided qualitatively by its convincing structure as well as quantitatively by its produced values. Of course: Even if the model seems to be configured well it not necessarily tells the truth about the system. But at least it can help to ask the right questions and get new ideas.